2005
DOI: 10.1080/10717540590921432
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Techniques of Biodegradable Implants Intended for Intraocular Application

Abstract: Polylactic acid and polylactic-co-glycolic acid are biocompatible and biodegradable polymers with wide utility for the design of controlled release systems for drugs. Regarding intraocular application, polymeric sustained-drug release systems are being studied to treat vitreoretinal diseases. Our work aimed to compare the influence of two implant manufacturing techniques, compression and hot molding, on the in vitro degradation of the polymeric matrices and on the release of dexamethasone acetate. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 16 publications
0
35
0
4
Order By: Relevance
“…However, this possibility needs to be tested since other researchers reported that the drug is homogeneously distributed within the device matrix (FIALHO & SILVA-CUNHA, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…However, this possibility needs to be tested since other researchers reported that the drug is homogeneously distributed within the device matrix (FIALHO & SILVA-CUNHA, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Os estudos pré-clínicos realizados mostraram uma liberação do fármaco, em quantidades adequadas, por um período de 8 semanas. Além disso, alterações nas estruturas oculares e na anatomia da retina não foram notadas durante o período de avaliação [100][101][102] . Em um projeto colaborativo entre os Laboratórios de Tecnologia Farmacêutica e o Laboratório de Engenharia de Polímeros e Compósitos da UFMG, foi desenvolvido um material polimérico biodegradável, preparado a partir do PU contendo PCL e/ou PEG.…”
Section: Medicamentos Transdérmicos (Adesivos)unclassified
“…Recently, Fialho and coworkers developed biodegradable implants containing PLGA and 1000 µg of dexamethsone for the treatment of inflammatory diseases in the posterior segment of the eye (Fialho, Silva-Cunha, 2005;Fialho et al, 2006). The developed implants were inserted into the vitreous of rabbits through pars plana.…”
Section: Biodegradable Implants In the Treatment Of Uveitismentioning
confidence: 99%